Early marriage, education and mental health: experiences of adolescent girls in Mozambique - Nhampoca, Joaquim M.; Maritz, Jeanette E. (Frontiers in Global Women's Health, 2024)
Introduction and background Early marriage and maternity represent a violation of human rights and a barrier to achieving gender equality in education. Studies conducted across various regions and countries, including Mozambique, have highlighted the negative consequences of early marriage and maternity, particularly on adolescent girls' physical, educational and mental health. Adolescent girls who marry before the age of 18 are more prone to a broad spectrum of mood, anxiety, and other psychiatric disorders. In the districts of Maganja da Costa and Morrumbala in Zambézia Province, Mozambique, high rates of early marriage persist despite government policies and interventions. Purpose statement This study aims to understand early marriage's socio-cultural, economic, and psychological drivers and impacts on adolescent girls' lives, focusing on education, mental health, and well-being. Design and methods This paper used a qualitative research design. We employed a life-story approach and used purposeful sampling to identify participants. Semi-structured interviews were conducted with 25 participants and the data were analysed using Tesch's thematic analysis approach. Results Elements contributing to early marriage and pregnancy are intricately linked with socio-cultural elements. These include the induction into specific societal roles, the affirmation of childbearing, the perceived importance of dowry, the impact of rite-of-passage ceremonies, and the cultural significance associated with a girl's initial menstruation. School dropout often originates from geographical and transportation challenges, nudging adolescent girls towards early marriage. In some instances, termination of pregnancy was viewed as a solution, while engaging in sexual activities was seen as a means to inject purpose into their lives or as a response to poverty. Positive changes and emotions were evident, yet regrettably, the ramifications of early pregnancy and marriage were primarily detrimental. These influenced the adolescent girls' interpersonal connections, educational and career opportunities, emotional well-being, and access to support networks. Conclusions The modern perspective, which advocates for equal educational rights for boys and girls and posits that marriage should occur after the age of 18, contradicts the socio-cultural perspective of adulthood. Contribution This study adds to the ongoing efforts to prevent and combat early marriage and maternity in Africa.